Birefringent crystal and preparation method and application thereof
By preparing Na6[ZnF2(B12O24H6)] birefringent crystals and utilizing the polarization of π-conjugated [BO3]3- units and Zn2+, the problems of insufficient transmittance and birefringence of existing birefringent crystal materials were solved, achieving optical performance with high transmittance and high birefringence, which is suitable for the preparation of birefringent optical devices.
Patent Information
- Application Number
- CN202511654054.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-12
- Publication Date
- 2026-02-03
AI Technical Summary
Existing classical birefringent crystal materials have shortcomings in terms of transmission range, transmittance, and birefringence, which limit their widespread use in optical applications.
The Na6[ZnF2(B12O24H6)] birefringent crystal was prepared by hydrothermal method. By combining π-conjugated [BO3]3- units, d10 transition metal cations Zn2+ and fluorine ions, a trigonal crystal system with a centrosymmetric structure was formed, which enhanced the anisotropy and birefringence of the material.
It achieves high transmittance in the wavelength range of 200-800nm, with an ultraviolet cutoff edge of 302nm, birefringence Δn=0.05@546nm, and thermal stability up to 380℃, making it suitable for fabricating birefringent optical devices.
Smart Images

Figure CN121451293A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of birefringent crystal materials technology, specifically relating to a birefringent crystal, its preparation method, and its application. Background Technology
[0002] Birefringent crystal materials are key components in the production of polarizing devices and laser elements. They can modulate and monitor the polarization of light along different optical axes in a bulk medium, playing a vital role in optical applications. Currently, classic birefringent crystal materials such as α-BaB₂O₄ (Δn = 0.124@546nm), YVO₄ (Δn = 0.0204@532nm), CaCO₃ (Δn = 0.172@564nm), and TiO₂ (Δn = 0.256@546nm) have been commercially applied. However, most of these birefringent crystals have some defects, limiting their widespread use in practical applications.
[0003] In recent decades, borates have attracted widespread attention due to their structural diversity and excellent performance characteristics. Among them, [BO3]... 3- As planar π-conjugated groups, [BO3] possesses high polarizability and optical anisotropy. Furthermore, the significant electronegativity difference between B and O atoms allows the material to exhibit a wide transmission band. 3- It is considered an ideal choice for constructing excellent birefringent crystals. Furthermore, fluoride ions (F...) - Not only does it possess the highest electronegativity, but it can also significantly enhance polarizability anisotropy and widen the HOMO and LUMO orbital gaps by adjusting the electronic structure of the material. Introducing fluoride ions enables the material to exhibit wider transmission and superior birefringence properties, making it more suitable for meeting the requirements of specific optical applications. Therefore, it is essential to develop novel borate crystal materials with excellent comprehensive performance by rationally utilizing the potential synergistic effects of different birefringent active building blocks. Summary of the Invention
[0004] The primary objective of this invention is to provide a birefringent crystal with advantages such as a wide transmission range (200-800 nm), high transmittance, a short ultraviolet cutoff edge (302 nm), a large birefringence (Δn = 0.05 @ 546 nm), and ease of growth.
[0005] Another object of the present invention is to provide a method for preparing the birefringent crystal.
[0006] Another object of the present invention is to provide a use for the birefringent crystal.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] This invention provides a birefringent crystal, the chemical formula of which is Na6[ZnF2(B 12 O 24 H6)], belonging to the trigonal crystal system, space group R-3c, cell parameters are . α=90°, β=90°, γ=120°.
[0009] The birefringent crystal provided by this invention has a zero-dimensional (0D) centrosymmetric structure. In its structure, B atoms coordinate with O atoms to form 6 [B(2)O3] planar triangles and 6 [B(1)O4] tetrahedra, while zinc coordinates with oxygen to form 2 [ZnO3F] tetrahedra; the [B(2)O3] planar triangles and [B(1)O4] tetrahedra are interconnected through shared vertices, forming a highly aggregated and symmetrical 6-MRS petal-shaped [B 12 O 24 [ZnO3F] structure; two [ZnO3F] tetrahedra embedded in 6-MRS petal-shaped [B] 12 O 24 The structure forms complete clusters, arranged parallel to the c-axis; Na, as a counter cation, occupies the gaps between these clusters. This invention will have a fully filled 3d... 10 electronic configuration of Zn 2+ Zn combines with highly electronegative fluorine atoms to form [Zn–O / F] coordination units with diverse structures. 2+ It exhibits strong polarizability and structural deformation capability. The formed [Zn–O / F] coordination units can construct various structural modes, from isolated polyhedra to one-dimensional chains, two-dimensional layers, and even three-dimensional frameworks. Its rich coordination geometry and controllable arrangement significantly enhance the anisotropy of the crystal, which is conducive to obtaining a large birefringence.
[0010] Furthermore, the range of B(1)-O bond lengths in the [B(1)O4] tetrahedron is as follows: The OB(1)-O bond angle ranges from 107.6(6) to 110.2(7)°; the B(2)-O bond length of the [B(2)O3] planar triangle is... The OB(2)-O bond angle is 116.7(7)-122.7(7)°; the Zn-O bond length of the [ZnO3F] tetrahedron is... The O-Zn-O bond angle is 115.62(12)°, and the Zn-F bond length is... The F-Zn-O bond angle is 102.25(17)°.
[0011] Furthermore, the oxidation states of B, Zn, and Na in the birefringent crystal are +3, +2, and +1, respectively.
[0012] Furthermore, the birefringent crystal is constructed by π-conjugation of [BO3]. 3- unit, d 10 transition metal cation Zn 2+ By integrating fluoride ions into the borate system, high birefringence and ultraviolet transmittance are obtained: its birefringence is Δn = 0.05@546nm; moreover, it has high transmittance in the wavelength range of 200-800nm, the ultraviolet cutoff edge is located at about 302nm, and the optical band gap is 4.10eV, which belongs to the indirect band gap compound.
[0013] Furthermore, the birefringent crystal exhibits an endothermic peak at around 403°C, indicating that it has a thermal stability of up to 380°C.
[0014] The present invention also provides a method for preparing the above-mentioned birefringent crystal, which uses a hydrothermal method to grow the crystal.
[0015] Furthermore, the hydrothermal crystal growth method includes the following steps:
[0016] A boron-containing compound, a zinc-containing compound, a fluorine-containing compound, and a sodium-containing compound are mixed evenly and then added to deionized water to obtain a mixed solution. The mixed solution is placed in a sealed environment and heated to crystallize, then cooled to room temperature, washed, and dried to obtain the final product.
[0017] Furthermore, the molar ratio of B, Zn, F, and Na in the boron-containing compound, zinc-containing compound, fluorine-containing compound, and sodium-containing compound is (20-22):1:1:(5-6).
[0018] Furthermore, the boron-containing compound is selected from boric acid or boron oxide; the zinc-containing compound is selected from any one of zinc oxide, zinc hydroxide, or water-soluble zinc salts; the fluorine-containing compound is selected from sodium fluoride or ammonium fluoride; and the sodium-containing compound is selected from any one of sodium hydroxide or sodium salts.
[0019] Furthermore, the water-soluble zinc salt is at least one of zinc nitrate, zinc fluoride, and zinc oxalate; the sodium salt is at least one of sodium fluoride, sodium carbonate, sodium nitrate, sodium oxalate, and sodium acetate.
[0020] Furthermore, the specific process of the temperature-raising crystallization is as follows: the temperature is raised to 220-230℃ at a rate of 50-60℃ / h and held for 50-60h.
[0021] Furthermore, the specific process of cooling to room temperature is as follows: cooling to room temperature at a rate of 1.5-2℃ / h.
[0022] The present invention also provides the application of the above-described birefringent crystal or the birefringent crystal prepared by the above-described preparation method in the preparation of birefringent optical devices.
[0023] Compared with the prior art, the main advantages of the present invention are as follows:
[0024] This invention provides a Na6[ZnF2(B 12 O 24 [H6] A birefringent crystal with a centrosymmetric structure, belonging to the trigonal crystal system and space group R-3c. Experimental results show that the birefringence of this crystal is Δn = 0.05@546nm, making it a potential birefringent crystal material; moreover, it belongs to an indirect bandgap compound with a bandgap of 4.10 eV. Furthermore, the birefringent crystal of this invention exhibits high thermal stability, reaching up to 380℃. In this invention, the birefringent crystal is prepared using a hydrothermal method, which is simple to operate, uses readily available raw materials, and allows for easy implementation of the preparation conditions. Attached Figure Description
[0025] Figure 1 Na6[ZnF2(B 12 O 24 Schematic diagram of the structure of H6)] crystal;
[0026] Figure 2 The Na6[ZnF2(B)] obtained in Example 1 12 O 24 EDS and SEM images of H6)] crystal;
[0027] Figure 3 The Na6[ZnF2(B)] obtained in Example 1 12 O 24 TG and DSC spectra of H6)] crystal;
[0028] Figure 4 The Na6[ZnF2(B)] obtained in Example 1 12 O 24 Ultraviolet-visible diffuse reflectance spectrum of H6)] crystal;
[0029] Figure 5 The Na6[ZnF2(B)] obtained in Example 1 12 O 24 The infrared spectrum of H6)] crystal;
[0030] Figure 6 The Na6[ZnF2(B)] obtained in Example 1 12 O 24 Raman spectrum of H6)] crystal;
[0031] Figure 7 The Na6[ZnF2(B)] obtained in Example 1 12 O 24 Image of birefringence measurement of H6)] crystal;
[0032] Figure 8Na6[ZnF2(B 12 O 24 The birefringence curve of the H6)] crystal calculated according to first principles;
[0033] Figure 9 Na6[ZnF2(B 12 O 24 Theoretical calculation of the band structure spectrum of H6)] crystal. Detailed Implementation
[0034] The technical solution of the present invention will be further described below with reference to specific embodiments. However, those skilled in the art should understand that the following embodiments are only for illustrating the present invention and should not be regarded as limiting the present invention. Specific conditions not specified in the embodiments are performed according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the reagents or instruments used are all conventional products obtained through commercial channels.
[0035] The crystals in this embodiment of the invention are grown using a hydrothermal method.
[0036] Example 1
[0037] A Na6[ZnF2(B 12 O 24 The preparation process of the H6)] birefringent crystal is as follows:
[0038] H3BO3 (0.300 g, 4.85 mmol), ZnO (0.0198 g, 0.24 mmol), NaF (0.0102 g, 0.24 mmol), and NaOH (0.0530 g, 1.3 mmol) were mixed thoroughly and then added to deionized water (0.1 mL) to obtain a mixture. This mixture was placed in a 25 mL high-temperature reactor lined with polytetrafluoroethylene and sealed. The reactor was then transferred to a programmable oven and heated to 220 °C at a rate of 60 °C / h, held at that temperature for 50 h, and then slowly cooled to room temperature at a rate of 1.7 °C / h to obtain a crude product. The crude product was washed with deionized water and dried to obtain colorless, transparent hexagonal blocky crystals Na6[ZnF2(B 12 O 24 H6).
[0039] Based on the Zn content, the birefringent crystal Na6[ZnF2(B)] obtained in this embodiment 12 O 24 The yield of H6)] is approximately 80%.
[0040] Example 2
[0041] A Na6[ZnF2(B 12 O 24The preparation process of the H6)] birefringent crystal is as follows:
[0042] B₂O₃ (0.168 g, 2.4 mmol), Zn(OH)₂ (0.0238 g, 0.24 mmol), NH₄F (0.008 g, 0.24 mmol), and NaF (0.058 g, 1.4 mmol) were mixed thoroughly and then added to deionized water (0.1 mL) to obtain a mixture. This mixture was placed in a 25 mL high-temperature reactor lined with polytetrafluoroethylene and sealed. The reactor was then transferred to a programmable oven and heated to 230 °C at a rate of 50 °C / h. After holding at this temperature for 55 h, the mixture was slowly cooled to room temperature at a rate of 1.5 °C / h to obtain a crude product. The crude product was washed with deionized water and dried to obtain colorless, transparent hexagonal blocky crystals Na₆[ZnF₂(B₂O₃, 2.4 mmol)] 12 O 24 H6).
[0043] Based on the Zn content, the birefringent crystal Na6[ZnF2(B)] obtained in this embodiment 12 O 24 The yield of H6)] is approximately 80%.
[0044] Example 3
[0045] A Na6[ZnF2(B 12 O 24 The preparation process of the H6)] birefringent crystal is as follows:
[0046] H3BO3 (0.326 g, 5.2 mmol), ZnCl2 (0.0312 g, 0.24 mmol), NaF (0.0102 g, 0.24 mmol), and NaNO3 (0.101 g, 1.2 mmol) were mixed thoroughly and then added to deionized water (0.1 mL) to obtain a mixed solution. This mixed solution was placed in a 25 mL high-temperature reactor lined with polytetrafluoroethylene and sealed. The reactor was then transferred to a programmable oven and heated to 225 °C at a rate of 55 °C / h, held at that temperature for 60 h, and then slowly cooled to room temperature at a rate of 2.0 °C / h to obtain a crude product. The crude product was washed with deionized water and dried to obtain colorless, transparent hexagonal blocky crystals Na6[ZnF2(B 12 O 24 H6).
[0047] Based on the Zn content, the birefringent crystal Na6[ZnF2(B)] obtained in this embodiment 12 O 24 The yield of H6)] is approximately 80%.
[0048] Crystal structure analysis
[0049] The structure of the crystal obtained in Example 1 was analyzed using single-crystal X-ray diffraction.
[0050] Single-crystal X-ray diffraction tests were performed on a SuperNova diffractometer. The crystal was attached to the end of a flat glass wire with AB glue. Crystal diffraction data were obtained using Mo-Kα rays. Data were collected at 293 K using a SuperNova CCD with ω-2θ detection. After processing with CrysAlisPro reduction software, absorption correction was performed using Multi-Scan, and single-crystal analysis was conducted using SHELXTL-2017 or Olex2. Traditional crystal structure analysis methods were used to determine the types and positions of atoms in the crystal. F... 2 The full matrix least squares plane is used to refine all atomic coordinates and anisotropic parameters.
[0051] Single-crystal X-ray diffraction results showed that the chemical formula of the crystal obtained in Example 1 was Na6[ZnF2(B 12 O 24 H6)], belonging to the trigonal crystal system, space group R-3c; its unit cell parameters are α = 90°, β = 90°, γ = 120°, crystal structure as follows Figure 1 As shown. Na6[ZnF2(B 12 O 24 The structure of the H6)] crystal is a zero-dimensional (0D) centrosymmetric structure. In its structure, B atoms coordinate with O atoms to form 6 [B(2)O3] planar triangles and 6 [B(1)O4] tetrahedra, and zinc coordinates with oxygen to form 2 [ZnO3F] tetrahedra; the [B(2)O3] planar triangles and [B(1)O4] tetrahedra are interconnected through shared vertices, forming a highly aggregated and symmetrical 6-MRS petal-shaped [B 12 O 24 [ZnO3F] structure; two [ZnO3F] tetrahedra embedded in 6-MRS petal-shaped [B] 12 O 24 The structure forms complete clusters, which are arranged parallel to the c-axis; Na occupies the gaps between these clusters as a counter cation. The B(1)-O bond length of the [B(1)O4] tetrahedron ranges from 1.442(9)- The OB(1)-O bond angle ranges from 107.6(6) to 110.2(7)°; the B(2)-O bond length of the [B(2)O3] planar triangle is 1.348(10)- The OB(2)-O bond angle is 116.7(7)-122.7(7)°; the Zn-O bond length of the [ZnO3F] tetrahedron is... The O-Zn-O bond angle is 115.62(12)°, and the Zn-F bond length is... The F-Zn-O bond angle is 102.25(17)°. These bond lengths and angles are similar to those reported in related metal borates. The calculated bond valences of B, Zn, and Na are 3.07, 1.92, and 1.12, respectively, indicating that the oxidation states of B, Zn, and Na are +3, +2, and +1, respectively.
[0052] The elemental composition of the crystal obtained in Example 1 was analyzed using energy-dispersive X-ray spectroscopy in a SU8010 scanning electron microscope. The results are as follows: Figure 2 As shown, the average molar ratio of its components is consistent with the chemical composition predicted by single-crystal X-ray diffraction.
[0053] Performance testing
[0054] (1) Thermogravimetric test
[0055] Thermogravimetric and differential scanning calorimetric analyses of the crystals obtained in Example 1 were performed on a Netzsch STA449C Jupiter instrument at 10°C / min in air. -1 The heating rate was measured, and the results are as follows: Figure 3 As shown. Figure 3 The TG curve shows that the crystal experiences a mass loss of approximately 7.7% between 383 and 453 °C. Furthermore, its DSC curve exhibits an endothermic peak around 403 °C, and the observed mass loss is consistent with the theoretical value of 7.1%. This indicates that the crystal possesses thermal stability up to 380 °C.
[0056] (2) Ultraviolet-Visible Diffuse Reflectance Spectroscopy Test
[0057] The UV-Vis diffuse reflectance spectra of the crystal obtained in Example 1 were measured using a Jasco V-650 spectrophotometer, and the results are as follows: Figure 4 As shown. By Figure 4 It can be seen that the crystal has high transmittance in the wavelength range of 200-800nm, the ultraviolet cutoff edge is located at about 302nm, and the optical band gap is 4.10eV, indicating that it belongs to ultraviolet birefringent crystal material.
[0058] (2) Infrared spectroscopy test
[0059] The infrared spectrum of the crystal obtained in Example 1 was measured on a VERTEX 70 Fourier transform infrared spectrometer, and the results are as follows: Figure 5 As shown. Figure 5 2400-3500cm -1 The absorption peak between these peaks is attributed to the OH stretching vibration; 1369 cm⁻¹ -1 The absorption peaks at 740 and 678 cm⁻¹ are attributed to the asymmetric stretching vibration of BO in the [BO₃] group. -1The absorption peaks at 1082 and 1026 cm⁻¹ are attributed to the bending vibration of BO in the [BO₃] group; -1 The absorption peak at 619 cm⁻¹ is attributed to the asymmetric stretching vibration of BO in the [BO₄] group. -1 The peak at that point is attributed to the bending vibration of BO in the [BO4] group, indicating that the crystal contains [BO3] and [BO4] groups.
[0060] (4) Raman spectroscopy test
[0061] The Raman spectroscopy of the crystal obtained in Example 1 was performed on a DXR03040430 spectrometer, and the results are as follows: Figure 6 As shown. Figure 6 Middle 0-1500cm -1 The characteristic spectral peaks between 2400 and 3500 cm⁻¹ are attributed to the stretching and bending vibrations of the BO group. -1 The spectral characteristic peaks between them belong to the OH stretching vibration.
[0062] (5) Measurement of birefringence
[0063] The birefringence properties of the crystal obtained in Example 1 were measured using a ZEISS Axio Scope polarization microscope. The test conditions were an A1 polarization microscope equipped with a Berek compensator, and a working wavelength of 546 nm. The birefringence (Δn) was determined according to the formula ΔR = Δn × T, where ΔR represents the optical retardation, Δn represents the birefringence, and T represents the sample thickness.
[0064] Birefringence measurement images as shown Figure 7 As shown. By Figure 7 It can be seen that the optical path difference (ΔR) at 546 nm is 608.91 nm, corresponding to a crystal thickness of 12.36 μm. Using the birefringence formula Δn = ΔR / T, the optical path difference of the Na6[ZnF2(B)] crystal obtained in Example 1 is measured to be... 12 O 24 The birefringence of H6)] at 546 nm is approximately 0.05. Figure 8 Na6[ZnF2(B 12 O 24 The birefringence curve of Na6[ZnF2(B)] crystal calculated according to first principles can be seen from the figure. 12 O 24 The birefringence (Δn) of the H6)] crystal at 546 nm is approximately 0.04, which is consistent with the experimental value.
[0065] (6) Theoretical Calculation
[0066] In order to study Na6[ZnF2(B 12 O 24The structure-property relationship of the H6)] crystal was calculated using the CASTEP package based on density functional theory (DFT) to determine its electronic structure and optical properties. The calculation results are as follows: Figure 9 As shown, this indicates that Na6[ZnF2(B 12 O 24 H6)] crystals belong to indirect bandgap compounds, and their theoretically calculated bandgap is 4.92 eV.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. Based on the present invention, some modifications or substitutions can be made, but these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of protection claimed by the present invention.
Claims
1. A birefringent crystal, characterized in that, The chemical formula of the birefringent crystal is Na6[ZnF2(B 12 O 24 H6)], belonging to the trigonal crystal system, space group R-3c, cell parameters are . α=90°, β=90°, γ=120°.
2. A method for preparing a birefringent crystal as described in claim 1, characterized in that, Crystals were grown using a hydrothermal method.
3. The method for preparing a birefringent crystal according to claim 2, characterized in that, The hydrothermal crystal growth method includes the following steps: A boron-containing compound, a zinc-containing compound, a fluorine-containing compound, and a sodium-containing compound are mixed evenly and then added to deionized water to obtain a mixed solution. The mixed solution is placed in a sealed environment and heated to crystallize, then cooled to room temperature, washed, and dried to obtain the final product.
4. The method for preparing a birefringent crystal according to claim 3, characterized in that, The molar ratio of B, Zn, F, and Na in the boron-containing compound, zinc-containing compound, fluorine-containing compound, and sodium-containing compound is (20-22):1:1:(5-6).
5. The method for preparing a birefringent crystal according to claim 3, characterized in that, The boron-containing compound is selected from boric acid or boron oxide; the zinc-containing compound is selected from any one of zinc oxide, zinc hydroxide, or water-soluble zinc salts; the fluorine-containing compound is selected from sodium fluoride or ammonium fluoride; and the sodium-containing compound is selected from any one of sodium hydroxide or sodium salts.
6. The method for preparing a birefringent crystal according to claim 5, characterized in that, The water-soluble zinc salt is at least one of zinc nitrate, zinc fluoride, and zinc oxalate; the sodium salt is at least one of sodium fluoride, sodium carbonate, sodium nitrate, sodium oxalate, and sodium acetate.
7. The method for preparing a birefringent crystal according to claim 3, characterized in that, The specific process of the temperature-raising crystallization is as follows: the temperature is raised to 220-230℃ at a rate of 50-60℃ / h and held for 50-60h.
8. The method for preparing a birefringent crystal according to claim 3, characterized in that, The specific process of cooling to room temperature is as follows: cooling to room temperature at a rate of 1.5-2.0℃ / h.
9. The application of the birefringent crystal as described in claim 1 or the birefringent crystal prepared by the preparation method as described in any one of claims 2-8 in the preparation of birefringent optical devices.